Stroke management in a university hospital in the largest South American city Manejo do acidente vascular cerebral em um hospital universitário na maior cidade da América do Sul - Adriana Bastos Conforto; Rodrigo Bomeny de Paulo; Cristiane Borges Patroclo; Samira Luísa dos Apóstolos Pereira; Helder de Souza Miyahara; Camila Barião da Fonseca; Fabio Iuji Yamamoto; Paulo Eurípides Marchiori; Eli Faria Evaristo; Milberto Scaff (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe characteristics and provision of care for patients admitted with cerebrovascular disorders (CVD), focusing on ischemic stroke (IS), in a large, public, academic hospital in São Paulo, Brazil. METHOD: We retrieved information about 357 patients with CVD admitted to the Neurology Emergency Department (NED) and Neurology Ward (NW) of our institution. We described patient characteristics and management of IS in NED and in NW. RESULTS: IS was diagnosed in 79.6% of CVD patients admitted to NED; 2.7% were submitted to thrombolysis. Extent of IS investigation and management were significantly different in NED and NW. CONCLUSION: IS patients in our center were younger than in developed countries. IS management was significantly influenced by patient characteristics. This information can aid in planning strategies to decrease stroke burden. OBJETIVO: Descrever características e manejo de pacientes internados com diagnóstico de doença cerebrovascular (DCV), enfocando principalmente o acidente vascular cerebral isquêmico (AVCI), em um hospital público universitário em São Paulo. MÉTODO: Coletamos informações de 357 pacientes com DCV internados no Pronto-Socorro de Neurologia (PSN) e na Enfermaria de Neurologia (EN) de nossa instituição. Descrevemos características dos pacientes e manejo do AVCI no PSN e na EN. RESULTADOS: O AVCI foi diagnosticado em 79,6% dos pacientes com DCV admitidos no PSN; 2,7% foram submetidos a trombólise. A extensão da investigação e o manejo da doença foram significativamente diferentes no PSN e na EN. CONCLUSÃO: os pacientes com AVCI em nosso centro foram mais jovens que em países desenvolvidos. O manejo do AVCI foi influenciado significativamente pelas características dos pacientes. Estas informações podem auxiliar no planejamento de estratégias para diminuir as conseqüências das DCV em nosso meio.